Geochemical and hydrocarbon generation evolution characteristics of marine-continental transitional facies shale: a case study of the Lower Permian Shanxi Formation in the Daning-Jixian area, eastern margin of Ordos Basin - Yangyang ZHANG; Yong LI; Xueying ZHANG; Liyuan LUO; Qingbo HE; Shuxin LI; Xiangjun LIU; Xiang LI; Xingtao LI; Qiang YANG; Shijia CHEN; Jungang LU; et al. (Shiyou shiyan dizhi, 2025)
To clarify the geochemical and hydrocarbon evolution characteristics of marine-continental transitional facies shale, the shale in the Lower Permian Shanxi Formation of the Daning-Jixian area in the eastern margin of the Ordos Basin was taken as the research object. By analyzing and determining total organic carbon (TOC) content, rock pyrolysis, kerogen carbon isotopes, maceral composition, paleontology, vitrinite reflectance (Ro), and conducting hydrocarbon generation thermal simulations, the study investigated the mineral composition, hydrocarbon source, generation potential, generation kinetics, and cumulative gas production rate calculation models of the shale in the Shanxi Formation. The results showed that: (1) The mineral composition of the shale in the Shanxi Formation of the Daning-Jixian area was mainly composed of quartz and clay minerals, with an average TOC content of 4.06%. The organic macerals were mainly composed of humic amorphous bodies and vitrinites, with an average Ro value of 2.61%. Overall, the shale was characterized by high organic matter abundance, dominated by humic-type organic matter, and was at an overmature stage of evolution, demonstrating high gas generation potential. (2) In a closed system, the maximum yields of gaseous hydrocarbons C1 and C1-5 from the shale in the Shanxi Formation were 138.74 and 139.22 mg/g, respectively. In a semi-closed system, the maximum yields of C1 and C1-5 were 86.51 and 102.59 mg/g, respectively, which were significantly lower than the maximum yields under closed conditions. (3) The activation energy for the generation of gaseous hydrocarbon C1 and C1-5 from the shale in the Shanxi Formation exhibited two distinct peaks, representing kerogen degradation and secondary cracking of heavy hydrocarbons. For C1, the two peaks of activation energy were 56 kcal/mol (26.53%) and 61 kcal/mol (30.10%), with a frequency factor of 2.0×1011 S-1. For C1-5, the two peaks of activation energy were 56 kcal/mol (28.45%) and 61 kcal/mol (19.18%), with a frequency factor of 2.2×1011 S-1. (4) The variation trend between cumulative gas production rate and Ro for the marine-continental transitional facies shale in the Shanxi Formation followed the pattern of a logistic function described by y=1/(1+e-x). Cumulative gas production rate calculation models for both the closed and semi-closed systems were established. The research results provide important theoretical support for the calculation of shale gas resources in marine-continental transitional facies and offer insights into favorable zone prediction.